2018
DOI: 10.1002/ecy.2201
|View full text |Cite
|
Sign up to set email alerts
|

Reliable estimates of beta diversity with incomplete sampling

Abstract: Beta diversity, the compositional variation among communities or assemblages, is crucial to understanding the principles of diversity assembly. The mean pairwise proportional dissimilarity expresses overall heterogeneity of samples in a data set and is among the most widely used and most robust measures of beta diversity. Obtaining a complete list of taxa and their abundances requires substantial taxonomic expertise and is time consuming. In addition, the information is generally incomplete due to sampling bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…This has been clearly pointed out for palaeontology (Forcino et al, 2015), but it can similarly be applied in ecology and biogeography. Beta diversity is affected by the completeness of the species lists, but reliable data and a correct ranking of the beta diversity measures can be achieved by using data on the most abundant species per site, a standard procedure in palaeobiology (Roden et al, 2018). In the case investigated here, the beta diversity patterns achieved by plot data matched those obtained from complete data, even if the latter were higher in terms of absolute values.…”
Section: Biogeographic Modelsmentioning
confidence: 80%
“…This has been clearly pointed out for palaeontology (Forcino et al, 2015), but it can similarly be applied in ecology and biogeography. Beta diversity is affected by the completeness of the species lists, but reliable data and a correct ranking of the beta diversity measures can be achieved by using data on the most abundant species per site, a standard procedure in palaeobiology (Roden et al, 2018). In the case investigated here, the beta diversity patterns achieved by plot data matched those obtained from complete data, even if the latter were higher in terms of absolute values.…”
Section: Biogeographic Modelsmentioning
confidence: 80%
“…Null models have also been highlighted as a useful tool for studying beta diversity that could be used to address sampling issues (Anderson et al 2011). For example, Roden et al (2018) used null models to demonstrate conditions under which beta diversity can be accurately estimated by focusing only on abundant taxa. Their conclusions rest on the assumption that patterns evident in dominant taxa can be extrapolated to the whole community; however, this may not be a suitable assumption for diverse pathogen or parasite communities in which rarer taxa can have ecological significance due to varying degrees of host-specialization and phenomena such as periodic host-switching (Brooks and Hoberg 2007; Woolhouse and Gaunt 2007; Ricklefs et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ߚ quantifies intraspecific spatial aggregation whilst controlling for the fraction of the estimated species pool in the samples (i.e., coverage). Others have suggested that beta-diversity should be calculated from only a subset of the most dominant species in a sample, but this approach still responds to changes in species pool size and the SAD (Roden et al, 2018). In contrast, our coverage-based method makes use of the SAD of the samples (i.e., the shape of the IBR curve) to make inferences for a constant fraction of the species pool.…”
Section: Discussionmentioning
confidence: 99%